KARAKTER PENYAIR DAN AKTIVIS WIDJI THUKUL SEBAGAI PEJUANG HAM DALAM PEMBELAJARAN SEJARAH - Rohani Tampubolon; Budi Purnomo; Anny Wahyuni (UNZAH Genggong, 2021)
This study aims to examine the courageous character of poet and activist Widji Thukul as a human rights fighter and the implications of his character in the study of History. This article uses historical research method with literature study approach, in data collection techniques researchers do by collecting written sources from books, journals, and the internet. And the steps taken by researchers in conducting this study are: heuristics, Verification, Interpretation and Histoirogafi. The results of this study show: (1) The background of activist Widji Thukul, (2) Activist Widji Thul human rights fighter (3) character implications in historical learning. Keywords: Background activist Widji Thukul; Activists, ; Human rights fighters; Character